ARE CDX2, BETA-CATENIN AND WNT IMMUNOMARCHERS USEFUL FOR EVALUATING THE CHANCE OF DISEASE PROGRESSION OR EVOLUTION TO DEATH IN PATIENTS WITH COLORECTAL CANCER? - Fabiola Pabst BREMER; Nicolau Gregori CZECZKO; Luiz Martins COLLAÇO; Letícia Elizabeth Augustin Czeczko RUTZ; Guilherme GIONEDIS; Camila Kienen YAMAKAWA (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2020)
ABSTRACT Background: Colorectal cancer (CRC) is one of the most common types of cancer in the world. Over time, intestinal epithelial cells undergo mutations that may lead to proliferative advantage and the emergence of cancer. Mutations in the beta-catenin pathway are amongst those described in the development of CRC. Aim: To verify the existence of a relation between the presence of Wnt3, beta-catenin and CDX2 in colorectal cancer samples and clinical outcomes such as disease progression or death. Method: Wnt3a, beta-catenin and CDX2 immunohistochemistry was performed on CRC tissue microarray samples (n=122), and analysis regarding the relation between biomarker expression and disease progression or death was performed. Results: No significant difference was found between the presence or absence of CDX2, beta-catenin or Wnt3a expression and clinical stage, tumor grade, disease progression or death. Conclusion: CDX2, beta-catenin and Wnt3a are not useful to predict prognosis in patients with CRC.